2021
DOI: 10.3390/ijerph181910348
|View full text |Cite
|
Sign up to set email alerts
|

Burden, Depression, and Awareness of Information on Safety Behavior in Korean Hemodialysis Patients during the COVID-19 Pandemic

Abstract: The purpose of this study was to investigate the relationships among burden, depression, awareness of information (AIC), and safety behavior among hemodialysis patients in Korea during the COVID-19 pandemic. The study participants included 149 patients who received hemodialysis at seven general hospitals in Korea between January and February 2021. A structured questionnaire was used to survey their levels of burden, depression, AIC, adherent safety behavior (ASB), and dysfunctional safety behavior (DSB). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We believe that the provision of short-term education did not improve the compliance of patient role behavior, considering that 55.6% of the experimental group of this study had been on dialysis for at least 5 years. However, a previous study [ 10 ] showed that in patients undergoing hemodialysis, the burdens of disease control (change in schedule for them to see a doctor and to receive treatment, dosing management, or change in the dialysis unit and hospital environment) were higher than the burdens of everyday life (schedule change, travel restrictions, unemployment, or income decline) due to the COVID-19 pandemic, and their willingness to be provided with education regarding dialysis tubing management was the same as that before the pandemic (63.1%). In another qualitative study [ 9 ], patients undergoing dialysis complained of anxiety and psychological fear of infection while undergoing dialysis due to vulnerable immunity and wanted to communicate with healthcare professionals regarding their diet, medication, symptoms during dialysis, and disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that the provision of short-term education did not improve the compliance of patient role behavior, considering that 55.6% of the experimental group of this study had been on dialysis for at least 5 years. However, a previous study [ 10 ] showed that in patients undergoing hemodialysis, the burdens of disease control (change in schedule for them to see a doctor and to receive treatment, dosing management, or change in the dialysis unit and hospital environment) were higher than the burdens of everyday life (schedule change, travel restrictions, unemployment, or income decline) due to the COVID-19 pandemic, and their willingness to be provided with education regarding dialysis tubing management was the same as that before the pandemic (63.1%). In another qualitative study [ 9 ], patients undergoing dialysis complained of anxiety and psychological fear of infection while undergoing dialysis due to vulnerable immunity and wanted to communicate with healthcare professionals regarding their diet, medication, symptoms during dialysis, and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Since the start of the COVID-19 pandemic, medical institutions have announced infection prevention guidelines and educational material, including the following information in dialysis units for infection control within said units: distance between beds, wearing personal protective equipment, equipment and environment management, waiting room closure, continuously wearing a mask during dialysis if it is not contraindicated, prohibition of food intake, adherence to respiratory hygiene etiquette, and restricting conversations between patients. Despite this, some patients do not follow these guidelines, including those on reducing snack consumption [ 9 ], and were still afraid of infection [ 7 ], and wanted to be educated by healthcare professionals on how to manage dialysis and to prevent infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research shows that 40% of the patients with MHD exist elevated anxiety symptoms (a SAS score of ≥ 50) in the early COVID-19 pandemic, and the severity of nearly 1/3 is moderate or higher (a SAS score of ≥ 60). The elevated anxiety syndrome of the patients with MHD during the outbreak is inseparable from the severity of the epidemic, the inconvenience and pressure caused by prevention and control management ( 10 , 11 , 14 , 22 ). The strict social isolation measures made it difficult for the patients and their families to travel, which caused increased worry about unaccompanied transfer in patients with MHD.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 19 (COVID-19), since its first outbreak in late 2019, has been a major public health exigency of international concern. The pandemic outbreak has posed a negative influence on the economy and health, and dramatically changed people's social and living environment, in addition to a threat to most of the patients worldwide ( 1 3 ). For instance, people were required to stay at home and maintain social distance for an extended period; in addition, discrimination, and violence against Asian and minority groups posed by the COVID-19 epidemic also broke out in many countries ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%